Dissecting the image of Elsa towards semiotic reading of the Philippine classic film ‘Himala’ - Ancheta, Jeffrey Rosario (Penerbit Universiti Kebangsaan Malaysia, 2016)
Himala (Miracle) is one of the Philippine classic films produced in 1982 by the Experimental Cinema of the Philippines. Aside from several local and international awards given to the film, it was also chosen as the Best Asia-Pacific Film of All Time in 2008 by the CNN and the Asia Pacific Screen Awards. The film narrates the story of Elsa, who induced the people of Cupang to believe that she had witnessed the apparition of the Virgin Mary in the hill during the eclipse. She also made the people believe that she can heal those who have diseases, that have resulted to many hopefuls flocking on her house. But who is Elsa? This paper focused on dissecting the character of Elsa to present new interpretations of the film. Through Roland Barthes’ Semiotic Theory, the study determined different images of Elsa such as Elsa is a god-like figure; Elsa is a curse, where the tough luck of Cupang came from; and Elsa is a religious prostitute that sells her so-called miracle for those who are hopeless. Using semiotics, it can be said that the film shows not only the socio-cultural, economic, and political issues in the country, but the dismantling of patriarchal society. The reading made to the character of Elsa shows the reconstruction of feminist culture in the film, which proves that women are more powerful than men.